"Dick and Carey Instructional Model and Creativity: Their Impact on Elementary Students’ Learning Outcomes - Sisri Wahyuni; Darmansya; Zelhendri Zen; Zuwirna (Jurnal Penelitian Pendidikan IPA, 2025)
This study investigates the influence of the Dick and Carey instructional model and students’ creativity on mathematics learning outcomes among elementary school students. Employing a quasi-experimental design with a 2×2 factorial structure, the research involved 51 fifth-grade students from two comparable schools in the Banuhampu District, West Sumatra. The experimental group received instruction using the Dick and Carey model, while the control group followed conventional teaching methods. Creativity was measured using a validated questionnaire, and learning outcomes were assessed through a posttest aligned with curriculum indicators. The results show that students taught using the Dick and Carey model achieved significantly higher learning outcomes than those taught conventionally. Furthermore, students with higher levels of creativity consistently outperformed their lower-creative peers in both instructional groups. However, statistical analysis indicated no significant interaction between instructional model and creativity level, suggesting the model’s universal applicability across diverse learner profiles. The study concludes that the Dick and Carey model is effective in enhancing mathematical understanding regardless of creativity level, offering a structured yet inclusive approach to classroom instruction. These findings provide valuable insights for teachers and curriculum developers aiming to optimize learning through systematic design and the integration of learner creativity.